2009
DOI: 10.1103/physrevlett.102.100402
|View full text |Cite|
|
Sign up to set email alerts
|

Vanishing Quantum Discord is Necessary and Sufficient for Completely Positive Maps

Abstract: Two long-standing open problems in quantum theory are to characterize the class of initial system-bath states for which quantum dynamics is equivalent to (i) a map between the initial and final system states, and (ii) a completely positive (CP) map. The CP map problem is especially important, due to the widespread use of such maps in quantum information processing and open quantum systems theory. Here we settle both these questions by showing that the answer to the first is "all", with the resulting map being … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
131
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(133 citation statements)
references
References 18 publications
2
131
0
Order By: Relevance
“…It has been used to understand the completely positive evolution of a system [17,18,19], local broadcasting [20,21]. Thus, finding zero discord quantum states is important in quantum information theory.…”
Section: Let {ρ (A)mentioning
confidence: 99%
“…It has been used to understand the completely positive evolution of a system [17,18,19], local broadcasting [20,21]. Thus, finding zero discord quantum states is important in quantum information theory.…”
Section: Let {ρ (A)mentioning
confidence: 99%
“…Several approaches have been proposed to quantify this generalized quantum correlation present in a bipartite mixed quantum state [5,[7][8][9], one of which, quantum discord [5], has received special attention [10][11][12][13][14][15][16]. Beyond the importance of nonclassical correlations (other than entanglement) for the foundations of quantum mechanics, the relevance of such an issue is increasing in several fields as well as in QIS applications.…”
mentioning
confidence: 99%
“…In the context of quantum field theory, it has been shown that the Unruh effect may also lead to an abrupt change in the behavior of correlations [17]. For applications in QIS, it is interesting to know that states with nonzero quantum discord cannot be locally broadcast [18], and this kind of nonclassicality is also related to a condition for a complete positive map [12]. Quantum discord was proposed as a figure of merit for the quantum advantage in some computational models without or with little entanglement [13,14].…”
mentioning
confidence: 99%
“…(49) that whenever ρ 0 = ρ 1 (which is the case when W 0 W 1 and K 0 K 1 ), the above commutator does not vanish and thus, as shown in [39], the state has nonvanishing quantum discord. Although it is not a sufficient condition, an initial state with nonvanishing discord indicates that the reduced spin dynamics (E and N ) may not be completely positive (CP) [40][41][42].…”
Section: Relativistic Quantum Mapmentioning
confidence: 99%